Hear Him Roar - Wingfield, Andrew (Utah State University, University Libraries, 2005)
A cougar attacks a jogger in the suburbs of a western city. Charlie Sayers, facing retirement as a wildlife biologist at a downsized state agency, is drawn into the search for the lion. He gets caught up in the conflict between wildlife habitat and an increasingly developed environment as, teetering between crisis and farce, he tries to piece together the puzzle of his own life.